Filing Timelines in Cross-Border Insolvency Proceedings Across Jurisdictions: A Comparative Study - Nishanthini R; Jayendra Kasture (PRAWO i WIĘŹ, 2025)
This study examines the timing of foreign insolvency filings in five jurisdictions: the United States of America, Australia, the European Union, the United Kingdom, and Singapore, which collectively experience a significant volume of cases worldwide. The current United Nations Commission on International Trade Law (UNCITRAL) Cross-Border Insolvency (CBI) law, established under the UNCITRAL, does not adequately implement the timing protocol under the determination of the Centre of Main Interests (COMI). The study addresses inconsistencies in applying the timing protocol, focusing on its uniformity, recognition standards, and relief measures through comparative analysis.